KARL MARX, TRABALHO, EDUCAÇÃO E LUTA PELO COMUNISMO | Karl Marx, work, education and the struggle for communism (Trabalho & Educação, 2018)
We will analyze the relation between the work process, education and human nature´s transformation in the work of Karl Marx. To analyze, above all, The capital, in which the German author shows that education plays a fundamental role in shaping a class of workers that takes capitalist production as presupposed. However, there is a fundamental contradiction regarding this process: the very development of the capitalist mode of production allows the emergence of potentialities that, with the suppression of capitalism, refer to a formative process of individuals no longer crumbled by the division of work, but multifaceted. Education, then, could have a rather distinct function after the suppression of capitalist system of production.___Buscaremos abordar a relação entre o processo de trabalho, a educação e a transformação da natureza humana na obra de Karl Marx. Analisaremos, sobretudo, O capital, tendo por objetivo mostrar que o autor alemão entende que a educação tem papel fundamental na conformação de uma classe de trabalhadores que toma a produção capitalista como suposto da sociabilidade. Procuraremos mostrar, no entanto, que a questão passa por uma contradição fundamental: o próprio desenvolvimento do modo de produção capitalista permite que surjam potencialidades que, com a supressão do capitalismo, remetem a um processo formativo de uma personalidade não mais esfacelada pela divisão do trabalho, mas multifacetada. A educação, então, poderia ter uma função bastante distinta daquela que tem no sistema capitalista de produção.